SHARIA FINANCING IN THE AGRICULTURAL SECTOR: SOLUTIONS TO THE PROBLEM OF USURY FROM A SOCIAL AND ECONOMIC PERSPECTIVE - Larasati, Pradipta Puspita; Fitriyah, Sayyidatul; Widiastuti, Tika; Berkah, Dian (Universitas Airlangga, 2017)
As an agricultural country, the agricultural sector has a vital role in the development of the national economy. But it does not mean the agricultural sector work without an obstacle. In fact the sector is often faced with various problems, especially in the weakness of capital. The capital needs will increase along with various choices of commodities and cropping patterns, the development of cultivation technology, post- harvest handling and processing of increasingly rapid results. In the era of agricultural technology, intensive of capital mobilization for both agricultural equipment and production facilities. Farmers can not afford to finance their farms with their own funds so that the farmers decide to finance the majority of which come from conventional lending institutions or even loan sharks and